2009
DOI: 10.1007/s10549-009-0502-2
|View full text |Cite
|
Sign up to set email alerts
|

HER2 signaling pathway activation and response of breast cancer cells to HER2-targeting agents is dependent strongly on the 3D microenvironment

Abstract: Development of effective and durable breast cancer treatment strategies requires a mechanistic understanding of the influence of the microenvironment on response. Previous work has shown that cellular signaling pathways and cell morphology are dramatically influenced by three-dimensional (3D) cultures as opposed to traditional two-dimensional (2D) monolayers. Here, we compared 2D and 3D culture models to determine the impact of 3D architecture and extracellular matrix (ECM) on HER2 signaling and on the respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
255
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(276 citation statements)
references
References 38 publications
19
255
1
1
Order By: Relevance
“…Cancer phenotypes such as loss of cell polarization, defective morphogenesis and enhanced invasion can be investigated in 3D collagen cultures, and alter the sensitivity of cancer cells towards inhibition of signalling molecules [38]. We found that depletion of MCT4 reduced the 3D growth of breast cancer cells but not non-malignant cells, suggesting that MCT4 supports the metabolic adaptation of cancer cells to these conditions.…”
Section: Discussionmentioning
confidence: 86%
“…Cancer phenotypes such as loss of cell polarization, defective morphogenesis and enhanced invasion can be investigated in 3D collagen cultures, and alter the sensitivity of cancer cells towards inhibition of signalling molecules [38]. We found that depletion of MCT4 reduced the 3D growth of breast cancer cells but not non-malignant cells, suggesting that MCT4 supports the metabolic adaptation of cancer cells to these conditions.…”
Section: Discussionmentioning
confidence: 86%
“…Alternatively, in vitro work has suggested that ECM can alter expression subtype markers, further confounding the link to prognosis [65,66] As a result, studies with different clinical samples can show very different results, and caution is needed in interpreting findings.…”
Section: Breast Cancer Subtypesmentioning
confidence: 99%
“…are known to cross regulate each other in stiff environments, potentiating both integrin signaling and often increasing receptor potency [107,[109][110][111]. Her2 is acutely regulated by FAK, such that ECM stiffening is a powerful regulator of Her2 and of Her2 resistance [65,110,112]. Adhesion to laminin-332 through a6b4 has also been linked to trastuzumab resistance through the transmembrane protein CD151 [113].…”
Section: Ecm and Chemotherapymentioning
confidence: 99%
“…Trastuzumab could be circumvented to varying degrees by alternate ErbB receptor targeting using, for example, alternate therapeutic antibodies such as Pertuzumab, or tyrosine kinase inhibitors (TKI) such as Lapatinib, or by a combination of antiErbB receptor antibodies and TKIs (12)(13)(14)(15). A number of clinical studies revealed evidence for efficient tumor-cell treatment with Lapatinib [reviewed in Ref.…”
mentioning
confidence: 99%